2021
DOI: 10.1002/er.7270
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinylidene fluoride‐co‐hexafluoropropylene) additive in perovskite for stable performance of carbon‐based perovskite solar cells

Abstract: The efficiency of perovskite devices is depending on the crystallization process with a controlled microstructure. Perovskite precursors with polymer additive significantly improve the perovskite film crystallinity, large grain boundaries, serve as passivating defect sites yielding increased power conversion efficiency (PCE). In this study, we improved the hole-transport free carbon-based perovskite solar cells by using polymer additive to passivate the perovskite grains with large size crystal and assist to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…These suggest that a suitable amount of P(VDF–TrFE) enhances the crystalline quality and suppresses the non-radiative recombination of perovskite films. 28–30 In contrast, with the further increase of the concentration to 5 mg mL −1 , the intensities of absorption and PL peak decrease, because P(VDF–TrFE) is the ferroelectric material with a large bandgap (4–5 eV) that cannot absorb the light with the wavelengths below 310 nm, 31,32 and a large amount of it would inevitably reduce the volume fraction of MAPbI 3 .…”
Section: Resultsmentioning
confidence: 99%
“…These suggest that a suitable amount of P(VDF–TrFE) enhances the crystalline quality and suppresses the non-radiative recombination of perovskite films. 28–30 In contrast, with the further increase of the concentration to 5 mg mL −1 , the intensities of absorption and PL peak decrease, because P(VDF–TrFE) is the ferroelectric material with a large bandgap (4–5 eV) that cannot absorb the light with the wavelengths below 310 nm, 31,32 and a large amount of it would inevitably reduce the volume fraction of MAPbI 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Narendhiran et al reported a method of using PVDF-HFP as an additive. 87 The high electronegative fluorine atoms in PVDF-HFP could combine with hydrogen atoms of the MA cation and form hydrogen bonds, which could reduce the nucleation rate during the crystallization process of the perovskite. In this way, the perovskite films showed enlarged grain sizes and improved crystallinity.…”
Section: Additive-controlled Growthmentioning
confidence: 99%
“…This significantly enhances the crystallinity and film quality by effectively retarding the process of perovskite crystal formation and aggregation during the initial nucleation stage. At the same time, due to the presence of the F---H bond, [87] Copyright 2021, Wiley-VCH. B,C) Reproduced with permission.…”
Section: Polymersmentioning
confidence: 99%
“…C) Environmental stability of PVDF-HFP-modified PSC devices. A) Adapted with permission [87]. Copyright 2021, Wiley-VCH.…”
mentioning
confidence: 99%